The Effect of Organization Culture On Job Satisfaction: The Case of Ayer Tena High School - Kiflu Chekole Tekle; Alemayehu Abera Lema; Kibur Girmachew Jiffar (Inkubis : Jurnal Ekonomi dan Bisnis, 2025)
Background: Organizational culture significantly influences employee job satisfaction, shaping attitudes, behaviors, and overall organizational effectiveness. While extensive research has established this relationship in various sectors, limited studies have examined multiple culture types simultaneously within educational institutions, particularly in developing regions. Objective: This study aims to examine the relationship between organizational culture and employee job satisfaction at SMA Ayer Tena Methods: This study used a census method with a questionnaire distributed to all 112 employees. The descriptive-explanatory quantitative approach shows that Clan Culture, Adhocratic Culture, Differentiation Culture, and Market Culture have a positive and significant relationship with employee job satisfaction. Results: On the other hand, the results revealed that Hierarchy Culture had a negative correlation with attitudes towards job satisfaction. This research can be of significant benefit to SMA Ayer Tena as a guide to improve the job satisfaction of faculty and school staff through the development of the right organizational culture to support the above factors. To refine the presented understanding of the relationship between organizational culture and future employee satisfaction, the researchers suggest that future investigations should be based on longitudinal research and utilize a larger and more diverse sample, as well as quantitative and qualitative data. Conclusion: This study concludes that organizational culture plays an important role in shaping job satisfaction. Clan culture, Adhocracy, and Market show a positive relationship with job satisfaction, while Hierarchical culture shows negative effects. These findings challenge bureaucracy-oriented cultural assumptions and emphasize the importance of collaborative, innovative, and performance-driven environments.